Cooperación judicial internacional sonorense - Flores Barraza, Eusebio F. (UNIVERSIDAD DE SONORA, 2017)
Over the past few years, especially in Sonora, we have been receiving letters rogatory or exhortations from other countries about civil cases and different subjects. This fact means, that we can deduce certains circumstances and characteristics from the international cooperation applied in the State courts, particularly, in the Supreme Tribunal of Justice of the State of Sonora, as an receptional office of letters rogatory and exhortations from abroad. Due to the nature of the process and the application of the Convention of 15 November 1965 on the Service Abroad of Judicial and Extrajudicial Documents in Civil or Commercial Matters and Convention of 18 March 1970 on the Taking of Evidence Abroad in Civil or Commercial Matters. From the bosom of the academy, we gave to ourselves the task to locate the mentioned letters rogatory for analyse in situ their process, and see that it is not quickly and easy in certain occasions. The development of the present work is the result of the cooperation from the General Secretary of Agreements of the Supreme Tribunal of Justice of the State of Sonora.